Implementasi Peraturan Bupati Sidoarjo Nomor 78 Tahun 2008 Tentang Pelimpahan Sebagian Kewenangan Bupati kepada Camat - Choiri Choiri; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2014)
The purposes of this research were to know implementation of law number 78 of 2008 on giving some authority from regent to sub-district head especially in Tanggulangin Sub-district. The methods of this research used qualitative discriptive. While, technique of collecting data through interview, observation, and documentation. Analysis data consists of data reduction, data presentation, and data verification. The result of this research showed that implementation of law number 78 of 2008 on giving some authority from regent to sub-district head didn’t optimal yet. Researchers still find the some important things should be given more attention and correction from the government of Tanggulangin Sub-districts level and government of Sidoarjo Regency.